Sobre la sintaxis de las oraciones de relativo: Un análisis de adjunción con estructura compartida - Krivochen, Diego Gabriel (Borealis – An International Journal of Hispanic Linguistics, 2022)
In this paper we examine existing analyses for relative clauses (mainly restrictive ones), and propose an analysis for Spanish relatives from the perspective of a lexicalised Tree Adjoining Grammar (TAG). We will provide a summary of the main proposals in the literature and examine the questions that any analysis of relative clauses should address. Our TAG approach synthesises the descriptive and theoretical advantages of existing models (the head external analysis, the raising analysis, and the matching analysis) and offers a solution to some of the main problems that have been observed in the literature. We will focus on the internal configuration of relative clauses, their structural position, and the category of the expression que in Spanish.